Environmentally Friendly Graphene Inks for Touch Screen Sensors. (16th June 2021) - Tkachev, Sergey; Monteiro, Miguel; Santos, João; Placidi, Ernesto; Hassine, Mohamed Ben; Marques, Pedro; Ferreira, Paulo; Alpuim, Pedro; Capasso, Andrea
Abstract: Graphene‐based materials have attracted significant attention in many technological fields, but scaling up graphene‐based technologies still faces substantial challenges. High‐throughput top‐down methods generally require hazardous, toxic, and high‐boiling‐point solvents. Here, an efficient and inexpensive strategy is proposed to produce graphene dispersions by liquid‐phase exfoliation (LPE) through a combination of shear‐mixing (SM) and tip sonication (TS) techniques, yielding highly concentrated graphene inks compatible with spray coating. The quality of graphene flakes (e.g., lateral size and thickness) and their concentration in the dispersions are compared using different spectroscopic and microscopy techniques. Several approaches (individual SM and TS, and their combination) are tested in three solvents ( N ‐methyl‐2‐pyrrolidone, dimethylformamide, and cyrene). Interestingly, the combination of SM and TS in cyrene yields high‐quality graphene dispersions, overcoming the environmental issues linked to the other two solvents. Starting from the cyrene dispersion, a graphene‐based ink is prepared to spray‐coat flexible electrodes and assemble a touch screen prototype. The electrodes feature a low sheet resistance (290 Ω □ −1 ) and high optical transmittance (78%), which provide the prototype with a high signal‐to‐noise ratio (14 dB) and multi‐touch functionality (up to four simultaneous touches). These results illustrate a potential pathway toward the integration of LPE‐graphene in commercial flexible electronics. Abstract : An efficient, inexpensive, and green strategy to produce graphene dispersions by liquid‐phase exfoliation with high concentration is proposed. By a combination of shear mixing and tip sonication techniques in cyrene solvent, a graphene‐based ink is made and spray‐coated to fabricate a touch screen sensor prototype with a high signal‐to‐noise ratio (14 dB) and multi‐touch functionality.